Framing the Iran-Israel Conflict: Ideological Representation in Al-Jazeera’s Nuclear News - Roziki, Khafid; Faisol, M; Hidayat, D; Sutaman, Sutaman (Makassar State University, 2025)
Abstract. This study applies discourse analysis to examine how Al-Jazeera portrays Iran's nuclear program, highlighting its language choices, narrative strategies, and ideological frameworks. The results show that Al-Jazeera forms a defensive narrative for Iran, emphasizing the threat from Israel while downplaying the image of Iran's nuclear ambitions. In its reporting, Al-Jazeera strategically uses terms such as